Analizar y Elaborar un Manual de Procesos de Mantenimiento de Mini cargadoras Automotrices - Vizuete Lema, Byron Norberto (2016)
The research analysis and development of a manual maintenance processes for mini automotive lifts, arises from the needs and problems faced by operators and mechanics working with these machines, which by virtue of their versatility and ease of use have proven to be of great utility in diverse activities related to the earthwork and other activities that require specific treatment that conventional machines do not have access. The research has been conducted based on an analysis of the problem set, to understand the global context has performed an analysis of comprehensive theoretical framework proposed based on the research variables, work was carried out based on the collaboration of companies the city of Riobamba that have mini loaders where a survey in which problems and difficulties greater impact on the use of mini loaders were established, the results obtained showed that there is a knowledge deficit in maintaining the applied machines, as well as the lack of technicians who perform the work, in some cases forcing shutdown, causing high costs. In response to these problems has raised a proposal to a model of preventive maintenance of efficient operation, maintenance understood as a system of several processes which vary in time and labor intensity based structure. The document proposed flows maintenance, necessary to carry out the processes and specific aspects of the maintenance component that have been translated into several tabs where you can find the task documentation, often working procedure together with the corresponding photographs, safety procedures, the necessary tools, spare parts to be used, materials, equipment and related comments. Finally it is considered that this manual will become a tool more services maintenance technicians and operators of mini loaders.